PENGARUH FINANCIAL TECHNOLOGY TERHADAP PERILAKU KEUANGAN DENGAN LITERASI KEUANGAN SEBAGAI VARIABEL INTERVENING PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Khofifah, Ana; Wahyuni, Ika; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Students as agents of change in dealing with social problems before finally joining the community. One of them is having good financial behavior in managing personal finances. The purpose of this study was to analyze and examine the effect of financial technology on financial behavior with financial literacy as an intervening variable. This research is an explanatory research. The population in this study were students of the Faculty of Economics and Business, Abdurachman Saleh University, Situbondo. The sampling technique used is proportional stratified random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that financial technology has a significant effect on financial literacy, financial technology has a significant effect on financial behavior, financial literacy has a significant effect on financial behavior. The results of the indirect effect hypothesis test show that financial technology on financial behavior through financial literacy has a significant positive effect.